Strategies used for the prevention and treatment of Burnout Syndrome (Research, Society and Development, 2021)
Objective: This study carried out an integrative review in order to identify the prevention and treatment of Burnout syndrome, as well as to analyze the response of this strategy. Methodology: A search was carried out on the journals portal, using the following descriptor-treatment and burnout., 73 abstracts were selected for reading and at the end 18 articles were included. Results: To prevent and treat Burnout syndrome, it is important to change the organization, the team's posture and the strengthening of individual coping. However, most studies select, mainly, in the field of the individual. For prevention, self-care strategy, early recognition of signs by colleagues, clinical supervision, modifications of stressors, training to help the individual deal with stressors, as well as changes, alterations seem to be important. For the treatment of exhaustion, cognitive behavioral therapy, emotional competence, group or individual psychotherapy, skills training, cohesion between peers, strong light, holistic method, acupuncture, art therapy and training courses aimed at changing attitudes contributed to improvement. of the syndrome. It is noteworthy that it is important to assess, in addition to work aspects, the impact of personal life on illness. Conclusion: In summary, it is important that the team knows the syndrome, that it is designed for prevention and recognition, as well as that it be returned to reduce stressors and strengthen personal relationships.